Informing adolescent substance misuse prevention: A parent focus group perspective - Hausheer, Robin (Journal of addictions & offender counseling, 2024)
Substance misuse during adolescence is an issue, and engaging parents in prevention efforts has significant positive impacts; yet barriers to engagement exist. The purpose of this qualitative parent focus group study was to understand the perspectives of participants (n = 5) about information and delivery platforms that will promote, engage, and support parents in prevention efforts. Thematic analyses identified five key themes from the semistructured interview: (1) educational support, (2) community support, (3) venues and platforms, (4) influences of other countries, and (5) potential barriers. Implications for clinical mental health and school counselors, and future research are discussed.